ChemInform Abstract: Asymmetric Organocatalytic Stepwise [2 + 2] Entry to Tetra‐Substituted Heterodimeric and Homochiral Cyclobutanes. Issue 46 (October 2016) - Nielsen, Alex J.; Jenkins, Hilary A.; McNulty, James
Abstract: Two reactants, both derived from cinnamic acids, are subjected to the optimized conditions to produce highly substituted head‐to‐tail coupled dimeric cyclobutane structures such as (III) bearing an aldehyde function.